Channel zero. Season one, Candle Cove [videorecording (DVD)] - Pniowsky, Abigail; Lehmann, Keenan; Forsyth, Amy, 1995- (Universal Pictures Home Entertainment, 2017)
A child psychologist investigates how the disappearance of his twin brother and other children many years ago is connected to a strange children's television show they used to watch at the time.